1970
DOI: 10.1017/s0043174500078553
|View full text |Cite
|
Sign up to set email alerts
|

Application of Herbicides in Foam

Abstract: We constructed a foam applicator capable of creating 300 to 400 gal of foam from 1 gal of water. The equipment was successful for applying herbicides in cotton (Gossypium hirsutum L., var. Stoneville 213) and soybeans (Glycine max Merr., var. Lee) after emergence. Weed control was equal with applications in foam as compared to conventional applications in water sprays. Foam production was highly dependent on the type and concentration of surfactant used. Various additives increased foam persistence in laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1973
1973
1993
1993

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Although plant growth regulating chemicals 2,3,5-triiodobenzoic acid (TIBA) and cytokinins in lanolin stimulate the development of new basal shoots from axillary buds of greenhouse rose plants, -spray applications fail to provide sufficient endogenous levels for the response (1,4,6). Zieslin et al (8) found the best branching response of 'Baccara' rose resulted from ethephon sprays when a thin score had been made above the basal axillary buds.…”
Section: Michigan State University East Lansingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although plant growth regulating chemicals 2,3,5-triiodobenzoic acid (TIBA) and cytokinins in lanolin stimulate the development of new basal shoots from axillary buds of greenhouse rose plants, -spray applications fail to provide sufficient endogenous levels for the response (1,4,6). Zieslin et al (8) found the best branching response of 'Baccara' rose resulted from ethephon sprays when a thin score had been made above the basal axillary buds.…”
Section: Michigan State University East Lansingmentioning
confidence: 99%
“…Low-expansion foams have been used as a carrier to reduce the spray drift of herbicides and plant growth retardants (5,6). Foam sprays enhance growth regulator uptake by providing close con tact for absorption between the chemical and plant during a longer period.…”
Section: Michigan State University East Lansingmentioning
confidence: 99%
“…Greenhouse weed control research with foam-applied herbicides demonstrated that 3-(3,4-dichlorophenyl)-l-methoxy-l-methylurea (linuron) and 3-(3,4dichlorophenyl)-I,I-dimethylurea (diuron) controlled morning glory (Ipomoea heleracea L.) and redroot pigweek (Anmaranthus retroflexus L.) more effectively if foam persistence were increased by covering treated plants with bell jars after treatment (9).…”
Section: Additional Index Words: Festuca Arundinaceamentioning
confidence: 99%